Assessing the role of insulin‐like growth factors and binding proteins in prostate cancer using Mendelian randomization: Genetic variants as instruments for circulating levels. Issue 7 (23rd June 2016) - Bonilla, Carolina; Lewis, Sarah J.; Rowlands, Mari‐Anne; Gaunt, Tom R.; Davey Smith, George; Gunnell, David; Palmer, Tom; Donovan, Jenny L.; Hamdy, Freddie C.; Neal, David E.; Eeles, Rosalind; Easton, Doug; et al.
Abstract : Circulating insulin‐like growth factors (IGFs) and their binding proteins (IGFBPs) are associated with prostate cancer. Using genetic variants as instruments for IGF peptides, we investigated whether these associations are likely to be causal. We identified from the literature 56 single nucleotide polymorphisms (SNPs) in the IGF axis previously associated with biomarker levels (8 from a genome‐wide association study [GWAS] and 48 in reported candidate genes). In ∼700 men without prostate cancer and two replication cohorts ( N ∼ 900 and ∼9, 000), we examined the properties of these SNPS as instrumental variables (IVs) for IGF‐I, IGF‐II, IGFBP‐2 and IGFBP‐3. Those confirmed as strong IVs were tested for association with prostate cancer risk, low (< 7) vs . high (≥ 7) Gleason grade, localised vs . advanced stage, and mortality, in 22, 936 controls and 22, 992 cases. IV analysis was used in an attempt to estimate the causal effect of circulating IGF peptides on prostate cancer. Published SNPs in the IGFBP1/IGFBP3 gene region, particularly rs11977526, were strong instruments for IGF‐II and IGFBP‐3, less so for IGF‐I. Rs11977526 was associated with high ( vs . low) Gleason grade (OR per IGF‐II/IGFBP‐3 level‐raising allele 1.05; 95% CI: 1.00, 1.10). Using rs11977526 as an IV we estimated the causal effect of a one SD increase in IGF‐II (∼265 ng/mL) on risk of high vs . low grade disease as 1.14 (95% CI: 1.00, 1.31). Because of the potential for pleiotropy of the genetic instruments, these findings can only causally implicate the IGF pathway in general, not any one specific biomarker. Abstract : What's New? Circulating insulin‐like growth factors (IGF) and their binding proteins have been associated with prostate cancer risk in observational epidemiological studies but it is not clear whether there is a causal relationship with disease. To address this question, the authors used Mendelian randomization, a method that uses genetic variants as proxies for measured exposures. Their results implicate the IGF pathway in general in prostate cancer development but specific biomarkers remain to be determined.